2016
DOI: 10.1038/nrurol.2016.225
|View full text |Cite
|
Sign up to set email alerts
|

The role of GATA2 in lethal prostate cancer aggressiveness

Abstract: Advanced prostate cancer is a classic example of the intractability and consequent lethality that characterizes metastatic carcinomas. Novel treatments have improved the survival of men with prostate cancer; however, advanced prostate cancer invariably becomes resistant to these therapies and ultimately progresses to a lethal metastatic stage. Consequently, detailed knowledge of the molecular mechanisms that control prostate cancer cell survival and progression towards this lethal stage of disease will benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 138 publications
4
71
0
Order By: Relevance
“…Our data indicate that knockdown of GATAe in PCs results in abnormal expression of different cancer and apoptosis-related genes in the adult Drosophila MTs. Our findings are in line with data from human GATA factors, which showed that GATA factors can act both as tumor suppressors or as oncogenes (Rodriguez-Bravo et al, 2017;Hellebrekers et al, 2009;Zheng and Blobel, 2010;Peters et al, 2014b).…”
Section: The Evolutionary Conservation Of Gata Factors In Relation Tosupporting
confidence: 91%
“…Our data indicate that knockdown of GATAe in PCs results in abnormal expression of different cancer and apoptosis-related genes in the adult Drosophila MTs. Our findings are in line with data from human GATA factors, which showed that GATA factors can act both as tumor suppressors or as oncogenes (Rodriguez-Bravo et al, 2017;Hellebrekers et al, 2009;Zheng and Blobel, 2010;Peters et al, 2014b).…”
Section: The Evolutionary Conservation Of Gata Factors In Relation Tosupporting
confidence: 91%
“…Upregulated GATA2 expression has been implicated in several tumour types, such as breast cancer [41], colorectal cancer [42] and liver cancer [43]. Moreover, recent studies con rmed that GATA2 overexpression in prostate cancer increases cellular motility and invasiveness, proliferation, tumorigenicity, and resistance to standard therapies [40]. In our study, high expression of GATA2 was signi cantly associated with better OS, especially in pathological grade + OC patients.…”
Section: Discussionsupporting
confidence: 67%
“…GATA2 is identi ed as a critical regulator of growth, differentiation and survival of hematopoietic stem cells [39,40]. Increasing evidence has shown that GATA2 expression is correlated with hematologic pathophysiologies and the proliferation and progression of solid tumors [40]. Upregulated GATA2 expression has been implicated in several tumour types, such as breast cancer [41], colorectal cancer [42] and liver cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…3) , Andreu-Vieyra et al 2011. GATA2 is an important mediator of androgen signaling within the hierarchical binding of other transcriptional regulators responsible for AR activity (Wang et al 2007, Jia et al 2008, Rodriguez-Bravo et al 2017) and has been shown to act downstream of FOXA1 in modulating AR binding to chromatin . FOXA1 has been further characterized as a pioneer factor for characterizing the AR and estrogen receptor (ER) cistromes in both prostate and breast cancer (Lupien et al 2008, Robinson et al 2011, Sahu et al 2011.…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 99%